Self-employment in Germany and Austria - Wank, Rolf (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The objective of the chapter is to analyse legal regulations concerning selfemployed activity in force in Germany and Austria. First and foremost, the author presents the scale of self-employment in the relevant countries and the sources of its legal regulation. He goes on to characterize the definition of a self-employed person and the categories of workers that fall within its scope. Furthermore, the author analyses the scope of protection guaranteed by German and Austrian legislation to the gainfully self-employed under individual and collective labour law. The last part of the chapter is devoted to the phenomenon of “bogus self-employment” and the legal mechanisms designed to combat it.